2023
DOI: 10.12790/ahm.22.0043
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome: correlation of the severity of the clinical picture and electrophysiological studies

Abstract: Purpose: This study aimed to correlate the severity of carpal tunnel syndrome (CTS) in terms of the clinical picture with electrophysiological studies to determine whether the severity could be predicted through one measure based on correlations with another.Methods: This cross-sectional correlational study enrolled 96 patients (139 hands) whose nerve conduction studies (NCS) confirmed the diagnosis of CTS, and to whom the Boston Carpal Tunnel Questionnaire (BCTQ) was administered to determine the subjective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The authors are well aware of the never-ending debate about the presence versus lack of correlation between clinical grade and EDX grade of severity of CTS. The most recent article is by Almigdad et al, 24 which finds a good correlation between the Boston Carpal Tunnel Questionnaire and EDX severity. The subjective scores based on patient’s symptoms are not considered sufficient to do a CTR by most surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors are well aware of the never-ending debate about the presence versus lack of correlation between clinical grade and EDX grade of severity of CTS. The most recent article is by Almigdad et al, 24 which finds a good correlation between the Boston Carpal Tunnel Questionnaire and EDX severity. The subjective scores based on patient’s symptoms are not considered sufficient to do a CTR by most surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences between the severity groups in duration of occupation (moderate/moderately severe = 20 years [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], severe = 25 years [7-30], P = 0.052), age (moderate/ moderately severe = 51.7 years (12.3), severe = 60.3 years (13.3), P < 0.001), and having hobbies (moderate/moderately severe = 37/ 564 (6.6%), severe = 11/49 (22.4%), P < 0.001) (Table 5). Patients who had been employed a longer duration in their occupation, were older, and had hobbies were more likely to have severe CTS by NCS.…”
Section: Comparing Combined Moderate and Moderately Severe Versus Sev...mentioning
confidence: 99%
“…BCTQ assesses symptom severity and functionality and is easy to apply. The correlation between these two tests has been previously studied, and in the literature, three studies found no correlation between ENMG and BCTQ, one study found a weak correlation, and one study found a significant correlation [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The total score of the SSS was classified into asymptomatic (11 points), mild (12-22 points), moderate (23-33 points), severe (34-44 points), and very severe (45-55 points). The total score of FSS was categorized into no difficulty (8 points), little difficulty (9-16 points), moderate difficulty (17-24 points), severe difficulty (25-32 points), and very severe (33-40 points) (11) . The control group was composed of seventy healthy participants (10 males and 60 females); they had no clinical or electrophysiological manifestations of CTS, and their age, gender, BMI, and geographical distribution were similar to the patients.…”
Section: Methodsmentioning
confidence: 99%